The Role of Green Financial Literacy in Enhancing Green Accounting Implementation Through Social CSR for MSME’s in Baubau City - Andriani Saputri; Misran; Irmawati Alimuddin (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study examines the effect of green financial literacy on green accounting and tests whether social corporate social responsibility (CSR) strengthens that relationship among MSMEs in Baubau City. The study addresses a gap in prior research, which has mostly discussed financial literacy, environmental accounting, and CSR separately, or has focused on large firms rather than MSMEs in a local emerging-economy setting. A quantitative explanatory design was employed. One hundred questionnaires were collected from MSME owners or managers through purposive sampling, and 86 valid responses were retained after data screening. The instrument measured green financial literacy, green accounting, and social CSR using a five-point Likert scale. Data were analysed with descriptive statistics, classical assumption tests, simple regression, and moderated regression analysis using SPSS 16. The findings show that green financial literacy has a positive and significant effect on green accounting. Social CSR also moderates the relationship, indicating that literacy is translated into greener accounting practices more effectively when MSMEs are supported by socially oriented CSR programmes such as mentoring, training, and business assistance. The study contributes by offering an integrated model that links internal capability and external institutional support in explaining green accounting adoption among MSMEs. Practically, the results imply that local governments, firms implementing CSR, and MSME support institutions should integrate green finance education with sustainability-oriented empowerment programmes